Islamic Human Resource Management (IHRM) Influence on Employee Turnover Intention in Multi-National Corporations (MNCs) in Malaysia - Bawasa, Salmi; Othman, Abdul Kadir (Information Management and Business Review, 2024)
This paper investigates the dynamics affecting employees’ intentions to leave their jobs in multinational corporations (MNCs) in Malaysia, focusing on the influencing factors of Islamic human resource management (IHRM). The increasing trends of employee turnover intention have significant implications for businesses, as they can impact strategic objectives and plans. The consequences encompass higher expenses, elevated costs for hiring and replacing employees, the need for time-consuming training, disruptions in productivity and supply, and a decrease in morale. To investigate this phenomenon, a positivist research design with a correlational study approach was adopted. The study population consisted of diversified MNCs, with a sample of 277 MNC employees as the unit of analysis. Questionnaires were used as the research instrument. The findings revealed a strong relationship between Islamic recruitment and hiring and employee turnover intention, and between Islamic performance and compensation and employee turnover intention. This study highlights the importance of integrating Islamic human resource management into organizational practices, identifying specific management strategies that can help mitigate and address employee turnover intention.